Severe hypocalcaemia following denosumab in a patient with cancer with vitamin D deficiency - Watthanasuntorn, Kanramon (BMJ Case Rep, 2018)
Denosumab is a monoclonal antibody that has been widely used for the prevention of skeletal-related events in patients with cancer with solid tumours and bone metastases, and acts by reducing the release of calcium from bones into the bloodstream. Severe hypocalcaemia is a rare and dangerous side effect of denosumab. We present a case of a patient with metastatic prostate cancer who developed severe hypocalcaemia after receiving a single dose of denosumab. Further laboratory analysis showed that the patient had a low vitamin D level, which contributed to the development of hypocalcaemia. He required an inpatient admission for repeated doses of intravenous calcium.